Penguatan Kesiapan Menyusui pada Ibu Hamil Trimester III melalui Edukasi Teknik Menyusui Berbasis E-Booklet di Wilayah Kerja Puskesmas Kelapa - Marleni Marleni; Gina Rizky Anggrayni (Jurnal Pengabdian Masyarakat Nusantara, 2026)
Limited readiness for breastfeeding among third-trimester pregnant women may affect the success of breastfeeding practices. Insufficient knowledge regarding proper breastfeeding techniques can lead to various lactation-related problems, including incorrect breastfeeding positions, poor infant attachment, and ineffective breastfeeding. Therefore, effective educational interventions are needed to improve breastfeeding readiness during pregnancy. This community service program aimed to strengthen breastfeeding readiness among third-trimester pregnant women through e-booklet-based education on breastfeeding techniques in the working area of Kelapa Community Health Center. The program was conducted in June 2025 and involved 20 third-trimester pregnant women. Educational activities were delivered through interactive lectures, discussions, question-and-answer sessions, and the distribution of e-booklets. Evaluation was carried out using pre-tests and post-tests to assess changes in participants’ knowledge and attitudes after the intervention. The results showed an improvement in participants’ knowledge, with the proportion of women in the good knowledge category increasing from 20.0% to 75.0%, while the poor knowledge category decreased from 30.0% to 0%. Positive attitudes toward breastfeeding also increased from 40.0% to 85.0% following the educational intervention. The use of e-booklets as educational media facilitated participants’ understanding of breastfeeding materials and enabled independent review of the information after the program. This community service activity demonstrates that e-booklet-based breastfeeding education is effective in improving knowledge, fostering positive attitudes, and strengthening breastfeeding readiness among third-trimester pregnant women